Optimization and CFD-RSM analysis of single orifice reactor for enhanced biodiesel production. - Fatemeh Khadivi; Bahram Hosseinzadeh Samani; Sajad Rostami; Kimia Taki; Mohammadreza Asghari; Shirin Ghatrehsamani (PLoS ONE)
Depleting fossil fuels necessitate innovative solutions for sustainable biodiesel production from sunflower oil, addressing global energy and environmental challenges. Computational Fluid Dynamics (CFD) with the k-ε model and Response Surface Methodology (RSM) optimized frequency (5-15 Hz), baffle diameter ratio (d₀/D: 0.4-0.8 mm), and baffle spacing (3-7 mm) in a single-orifice oscillatory flow reactor (OFR). Optimal conditions (frequency = 12.12 Hz, d₀/D = 0.4 mm, spacing = 10 mm) achieved an 83% biodiesel conversion, maximum turbulent kinetic energy (TKE) of 7.56 m²/s², maximum vorticity of 112.23 1/s, and energy dissipation of 359.82 m²/s³, validated by a TKE-yield correlation (R² = 0.972). Simplified reactor design reduces energy dissipation by 20% compared to multi-orifice reactors (88% yield, higher costs) and smooth periodic constriction reactors (74.5% yield). Findings offer a scalable, eco-friendly solution for industrial biodiesel production, minimizing fossil fuel dependency and enhancing process efficiency.